Effects of Teaching Students through Problem-Solving on Students’ Academic Performance in Problem-Solving - Emmanuel Acquandoh; Zakari Zunurain; Dennis Offei Kwakye; Samuel Redeemer Adornyo (Jurnal Gantang, 2022)
The study aimed to determine how teaching students problem-solving techniques affected their academic problem-solving performance. A quasi-experimental research design was used for this study. The BIA Lamplighter College of Education's level 400 students make up the population for the 2022–2023 academic year. However, all upper primary students were chosen for the study because Problem-solving was a subject taught in that grade. There were three groups of 126 upper primary students in total. Intact groups were used in the study. The problem-solving technique was used in conjunction with the whole class, cooperative, and think-pair-share teaching methods while teaching Groups 1, 2, and 3 (G1, G2, and G3). Scores from the pre-and post-tests were used to gather information. The data were analyzed using ANOVA, Wilcoxon Signed Ranks, Kruskal-Wallis Test, both Wilcoxon W and Mann-Whitney U. The study's conclusions suggest that teaching through Problem-solving may enhance students' problem-solving abilities. The study also discovered that both students taught using whole-class teaching strategies and students led using cooperative learning and think pair teaching strategies benefit from the techniques. After using the "teaching through" problem-solving approach, there was no discernible difference in performance between male and female students.